2018
DOI: 10.1007/978-3-030-01270-0_20
|View full text |Cite
|
Sign up to set email alerts
|

On the Solvability of Viewing Graphs

Abstract: A set of fundamental matrices relating pairs of cameras in some configuration can be represented as edges of a "viewing graph". Whether or not these fundamental matrices are generically sufficient to recover the global camera configuration depends on the structure of this graph. We study characterizations of "solvable" viewing graphs, and present several new results that can be applied to determine which pairs of views may be used to recover all camera parameters. We also discuss strategies for verifying the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(72 citation statements)
references
References 24 publications
(87 reference statements)
2
70
0
Order By: Relevance
“…Fig. 1: Viewing graphs with eight vertices that were left undecided in [16] and that we determined to be solvable.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 1: Viewing graphs with eight vertices that were left undecided in [16] and that we determined to be solvable.…”
Section: Related Workmentioning
confidence: 99%
“…This analysis was later extended in [19], where it was shown that some solvable graphs can be constructed starting from a triangle and adding vertices of degree two one at a time. More recently, Trager et al [16] provided some necessary conditions and a new sufficient condition for graph solvability. Their results permit to completely characterize graphs with at most seven vertices.…”
Section: Related Workmentioning
confidence: 99%
“…Heyden and Åström [12] and Trager et al [21] show that when the camera foci are not all on a plane, the bifocals are necessary and sufficient to cut out the multiview variety. There has also been work to further reduce this description by considering the minimal number of bifocals needed ( [12], [23]), though we will not address this question here. In this section, we focus on the ideal-theoretic relationship between the bifocal ideal H 2 A and the multiview ideal M A when the camera foci are noncoplanar.…”
Section: The Bifocal Idealmentioning
confidence: 99%
“…A number of papers analyze the solvability of SfM by investigating its corresponding viewing graph, in which each node represents a camera and edges represent available fundamental matrices [16,20,23,29,30]. These approaches, however, assume that the cameras are in general position and hence do not determine which viewing graphs are solvable in (possibly partly) collinear settings.…”
Section: Related Workmentioning
confidence: 99%